2020
DOI: 10.4491/eer.2020.375
|View full text |Cite
|
Sign up to set email alerts
|

Experimental analysis on the synergistic effect of combined use of ozone and UV radiation for the treatment of dairy industry wastewater

Abstract: The present study focused on the various advanced oxidation processes; Ozone, UV radiation, O 3 /H 2 O 2 , O 3 /UV, UV/H 2 O 2 and O 3 /UV/H 2 O 2 for treatability of dairy industry wastewater. With this aim, the trials were carried out in cylindrical reactor fortified with UV radiation and Ozone injection. Efficiency of the treatment process was evaluated considering Chemical Oxygen Demand (COD), lactose reduction and process parameters were determined to be reaction time, pH, circulation rate, and H 2 O 2 do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The AOP could generate strong oxidizing agents (such as hydrogen peroxide, hydroxyl radicals, atomic oxygen, oxygen and hydrogen peroxide), which will tend to remove more vulnerable pollutants present in effluent (Magureanu et al, 2008; Mejía‐Morales et al, 2020). AOP processess such as ozone, UV, fenton and catalytic process alone in the treatment of dairy effluent did not provide any possible results in treatment efficiency, which is reported in a previous study (Suresh et al, 2020). Electrical discharge plasma method is one of the AOP methods that intensively removes severe pollutants present in effluent (Yu et al, 2017).…”
Section: Introductionmentioning
confidence: 54%
“…The AOP could generate strong oxidizing agents (such as hydrogen peroxide, hydroxyl radicals, atomic oxygen, oxygen and hydrogen peroxide), which will tend to remove more vulnerable pollutants present in effluent (Magureanu et al, 2008; Mejía‐Morales et al, 2020). AOP processess such as ozone, UV, fenton and catalytic process alone in the treatment of dairy effluent did not provide any possible results in treatment efficiency, which is reported in a previous study (Suresh et al, 2020). Electrical discharge plasma method is one of the AOP methods that intensively removes severe pollutants present in effluent (Yu et al, 2017).…”
Section: Introductionmentioning
confidence: 54%
“…Studies have also observed its applications (as individual and hurdle techniques) for air purification or disinfection, biofilm inactivation, sterilization of dairy equipment, and sanitation of dairy farms and processing areas (Masotti et al, 2019;Suresh et al, 2021;Heacox, 2014). hazardous to consumers' health (Varga and Szigeti, 2016).…”
Section: Additional Applications Of Ozone In the Dairy Sectormentioning
confidence: 99%
“…However, optimizing factors, such as ozone concentration and treatment time, is necessary for each product. Other than the inactivation treatment, additional applications of ozone treatment include de-sludge treatment, wastewater processing, food contact surface and air disinfection, biofilm elimination, and reduction of toxins and antibiotics in milk (Khoori et al, 2020;Masotti et al, 2019;Sert and Mercan, 2021b;Suresh et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation